(untitled) (Research, Society and Development, 2020)
The Geographical Indication (GI) refers to a quality attributed to a product originating in a territory whose characteristics are inherent to its geographical origin. The objective of this work was to define the elements of the physical environment (biotic, abiotic and their associations) on the quality melate honey from the bracatinga of the Planalto Sul Brasileiro, to compose the dossier sent to the National Institute of Industrial Property (INPI) for the GI request. For this, the characteristics of bracatinga were described (natural environment, sap quality, genetics, abiotic factors), of symbiosis and synergism with microorganisms, of parasitism by mealybug, of trophobiosis between ants and mealybugs, of fumagina, of bees, beekeeper and land use. Bracatinga melate honey, a product of unparalleled quality, is the result of a set of biotic and abiotic factors, highlighting the relationship between the bee Apis melífera and mealybug (Tachardiella sp.). The characterization of the physical elements proves the specificities observed in the Planalto Sul Brasileiro and serves as a subsidy to compose the dossier requesting the appellation of origin from the INPI.